Attributes influencing clothing store choice for an emerging market's Generation Y Twixter customers. Issue 2 (15th March 2018) - Thompson, Kim Helen; Ellis, Debbie; Soni, Sanjay; Paterson, Samantha
Abstract: The aim of this paper was to determine the key attributes influencing a sub-segment of Generation Y, the Twixters' choice of clothing retailers in South Africa, an emerging market. Generation Y has been identified as an important segment particularly for apparel and the Twixter sub-group comprises a third of the segment. Using a positioning theory lens, retailers need to understand the attributes a target market finds important as stores are positioned in consumers' minds on those attributes. The study therefore sought to determine what these Twixters consider to be important attributes in their clothing store selection. The study comprised two stages; a qualitative stage based on focus group discussion data in which the attributes were determined, discussed and defined, and a quantitative stage, which involved a survey administered to 368 Twixter respondents which determined the relative importance of the attributes to Twixters in their clothing store selection. The results reveal that these Twixters appreciate the price–quality relationship and prefer clothing stores which provide high quality, unique and fashionable merchandise that meets their value for money requirements. The results of the study, although not generalisable, provide noteworthy insight for clothing store and apparel marketers targeting these Generation Y customers.